Study of the Etiological Causes of Toe Web Space Lesions in Cairo, Egypt - Hussein Mohamed Hassab-El-Naby; Yasser Fathy Mohamed; Hamed Mohamed Abdo; Mohamed Ismail Kamel; Wael Refaat Hablas; Osama Khalil Mohamed (Dermatology Research and Practice)
Background. The etiology of foot intertrigo is varied. Several pathogens and skin conditions might play a role in toe web space lesions. Objective. To identify the possible etiological causes of toe web space lesions. Methods. 100 Egyptian patients were enrolled in this study (72 females and 28 males). Their ages ranged from 18 to 79 years. For every patient, detailed history taking, general and skin examinations, and investigations including Wood’s light examination, skin scraping for potassium hydroxide test, skin swabs for bacterial isolation, and skin biopsy all were done. Results. Among the 100 patients, positive Wood’s light fluorescence was observed in 24 and positive bacterial growth was observed in 85. With skin biopsy, 52 patients showed features characteristic for eczema, 25 showed features characteristic for fungus, 19 showed features characteristic for callosity, and 3 showed features characteristic for wart while in only 1 patient the features were characteristic for lichen planus. Conclusion. Toe web space lesions are caused by different etiological factors. The most common was interdigital eczema (52%) followed by fungal infection (25%). We suggest that patients who do not respond to antifungals should be reexamined for another primary or secondary dermatologic condition that may resemble interdigital fungal infection.